Exosomal transfer of miR-501 confers doxorubicin resistance and tumorigenesis via targeting of BLID in gastric cancer. (10th September 2019) - Liu, Xu; Lu, Ying; Xu, Yunchao; Hou, Sizhu; Huang, Jinli; Wang, Bo; Zhao, Jinyao; Xia, Shilin; Fan, Shujun; Yu, Xiaotang; Du, Yue; Hou, Li; et al.
Abstract: Exosomal transfer of oncogenic miRNAs can enhance recipient cell growth, metastasis and chemoresistance. Currently we found that microRNA-501-5p (miR-501) was overexpressed in doxorubicin-resistant gastric cancer (GC) SGC7901/ADR cell-secreted exosomes (ADR Exo) than that in SGC7901 cell-secreted exosomes (7901 Exo). ADR Exo was internalized by SGC7901, and a Cy3-miR-501 mimic was transferred from SGC7901/ADR to SGC7901 via exosomes. ADR Exo conferred doxorubicin resistance, proliferation, migration and invasion abilities to negative control miRNA inhibitor-expressing GC cells, whereas it inhibited apoptosis. MiR-501 knockdown or BH3-like motif-containing protein, cell death inducer (BLID) overexpression could reverse the effects of ADR Exo on recipient cells. SGC7901 cells cocultured with SGC7901/ADR prior to treatment with GW4869 or transfection of a miR-501 inhibitor were sensitive to doxorubicin and exhibited attenuated proliferation, migration and invasion and increased apoptosis. The intratumoral injection of ADR Exo into negative control miRNA inhibitor-expressing SGC7901 cells induced rapid subcutaneous tumor growth and resistance to doxorubicin compared to that of miR-501 knockdown or BLID-overexpressing cells. This effect is possibly achieved by exosomal miR-501-induced downregulation of BLID, subsequent inactivation of caspase-9/-3 and phosphorylation of Akt. Exosomal miR-501 might be a therapeutic target for GC. Highlights: Horizontal transfer of exosomal miR-501 enhances recipient cell doxorubicin resistance by targeting BLID. Exosomal miR-501-mediated BLID downregulation suppresses apoptosis of recipient cells through inactivating caspase pathway. Exosomal miR-501 downregulates BLID to promote recipient cell proliferation, migration, and invasion via Akt phosphorylation. Exosomal miR-501 might serve as a novel therapeutic target for gastric cancer.